9t = 27.99
5t = ?
Cross-multiply : 9t? = 139.95t
?=15.55
First, 9.8 (Gravity) times 3 (time) equals 29.4, which is the velocity after 3 seconds. The kinematic equation for change in position that uses the variables we have is:
delta x= (v)(t) -0.5(acceleration)(time)^2
delta x= 29.4 times (3) - 0.5 (9.8) times 9
delta x= 44.1
100 minus 44.1 equals 55.9, which is the answer for part a.
Tell me if you need any clarification
PART B:
The kinematic equation for this is:
delta x= (initial velocity) times time plus 0.5 (a)(time)^2
100=(0)times(x) plus 0.5 (a)(time)^2
100=0.5(9.8)(x)^2
100=4.9x^2
100/4.9 is approxamitely 20.4.
The squareroot of this is approxamitely 4.5.
4.5 seconds
Tell me if you need any clarification
Check out the picture I've got the full explanations on there
Hope it's clear
The length of rope(consist of 3 pieces)=9*2=18m
One piece=18/3=6m
Pls mark me as the Brainliest as I really need it!